2018
DOI: 10.1108/jerer-06-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of volatility and equity market uncertainty on herd behaviour: evidence from UK REITs

Abstract: Purpose This paper aims to examine herding behaviour among investors and traders in UK-listed Real Estate Investment Trusts (REITs) within three market regimes (low, high and extreme volatility periods) from the period June 2004 to April 2016. Design/methodology/approach Observations of investors in 36 REITs that trade on the London Stock Exchange as at April 2016 were used to analyse herding behaviour among investors and traders of shares of UK REITs, using a Markov regime-switching model. Findings Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Therefore, herding behavior implies that security dispersions (i.e. CSADt) will decrease with the absolute value of the market return, since each asset becomes similar with regard to sensitivity to the market return (Akinsomi et al, 2018). Chang et al (2000) suggested that during periods of market stress, one would expect return dispersion (i.e.…”
Section: Csad Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, herding behavior implies that security dispersions (i.e. CSADt) will decrease with the absolute value of the market return, since each asset becomes similar with regard to sensitivity to the market return (Akinsomi et al, 2018). Chang et al (2000) suggested that during periods of market stress, one would expect return dispersion (i.e.…”
Section: Csad Calculation Methodsmentioning
confidence: 99%
“…In the figure , {𝑆 } denotes the sample path of a first-order, 𝛽 : denotes transition probability parameter vectors and two transition probabilities are time varying, evolving as logistic functions of 𝑥′ 𝛽 , 𝑖 = 0,1 , where the (𝑘𝑥1) conditioning vector 𝑥 contains economic variables that affect the state transition probabilities (Diebold et al, 1994). The main advantage of the TV-MS model against the constant transition probability specification is that it allows the duration of herd behavior to vary across different regimes of market volatility (Akinsomi et al, 2018). It also allows determination of the effect of economic policy uncertainty and market sentiment, as measured by the US Daily News Index (EPU).…”
Section: Figure 1 Transition Probabilities Matrixmentioning
confidence: 99%
“…The increasing popularity of REITs in many major European markets has resulted in a considerable number of empirical studies concentrated on their respective qualitative and quantitative investment characteristics. For example, in Spain (Marzuki and Newell, 2018), Germany (Newell and Marzuki, 2018), the UK (Akinsomi et al, 2018;Jadevicius and Lee, 2017;Newell and Marzuki, 2016), Belgium (Marzuki and Newell, 2019), Turkey (Erol and Tirtiroglu, 2011) and France (Newell et al, 2013 significance of REITs has attracted considerable research interest with a number of studies on Irish REITs scrutinising the crucial role of REITs in the post-GFC recovery, such as their role in stimulating the private rented sector of the Irish housing segment (Duffy et al, 2017) and as an exit mechanism to offload property assets (Mercille and Murphy, 2016). However, an empirical analysis of the investment attributes of Irish REITs is yet to be documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for this argument in the case of Brexit uncertainty (Schiereck et al 2016, Akinsomi et al, 2018.…”
Section: Resultsmentioning
confidence: 98%